Description of Simulium damascenoi (Diptera: Simuliidae) male and the black-fly species from the State of Amapá, Brazil - Neusa Hamada (Memórias do Instituto Oswaldo Cruz., 2003)
Five species are included in the Simulium siolii group, which is placed in the subgenus Psaroniocompsa (Diptera: Simuliidae). Of these five species, only two (Simulium siolii Py-Daniel and Simulium tergospinosum Hamada) have been described in all their life stages, except eggs. Knowledge of the taxonomic characters of all life stages of a species is important in order to clarify interspecific and higher-level taxonomic relationships. The objectives of the present study are to describe the male of Simulium damascenoi Py-Daniel, to provide a list of black-fly species their bionomics and distributions in the state of Amapá, Brazil, and to provide an identification key for larvae and pupae for these species.